2022
DOI: 10.3390/ijms232012641
|View full text |Cite
|
Sign up to set email alerts
|

Association between Changes in the Patterns of Antinuclear Autoantibodies during Immune Checkpoint Inhibition Therapy and the Development of Severe Immune Related Adverse Events

Abstract: Immune-related adverse events (irAEs) are unpredictable autoimmune-like toxicities induced by immune checkpoint inhibitors (ICI). irAEs are a consequence of a breakdown in self-tolerance. ICIs can induce autoantibody formation, and the presence of antinuclear autoantibodies (ANAs) has been reported in patients who developed irAEs. Our goal was to compare ANA patterns by indirect immunofluorescence at different timepoints before (baseline) and after the initiation of ICI treatment and to analyze the role of ANA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Studies have not established a clear relationship between elevated autoantibodies and incidence of irAEs, and contradictory results exist regarding their impact on patient outcomes. 19,21,22 Notably, our patient initially presented with Raynaud's phenomenon, which is typically associated with mixed connective tissue disease. 23 It is challenging to determine whether our patient's Raynaud's phenomenon was related to the immune dysregulation of TC or represented a predisposition to autoimmunity that was further exacerbated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Studies have not established a clear relationship between elevated autoantibodies and incidence of irAEs, and contradictory results exist regarding their impact on patient outcomes. 19,21,22 Notably, our patient initially presented with Raynaud's phenomenon, which is typically associated with mixed connective tissue disease. 23 It is challenging to determine whether our patient's Raynaud's phenomenon was related to the immune dysregulation of TC or represented a predisposition to autoimmunity that was further exacerbated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Toi et al 44 found that the presence of pre‐treatment anti‐nuclear autoantibodies (ANA), RF or anti‐thyroid autoantibodies predicted irAEs overall, independent of organ type, suggesting that the presence of autoantibodies may be a harbinger of a predisposition toward irAEs. Yet there is also an observation that the development of autoantibodies after ICI treatment may portend more severe irAEs, this has been described in most depth in the context of ANA seroconversion 45 . Lastly, there is also evidence that ICI influence the B‐cell compartment and that these changes may promote ICI‐induced irAEs 46 .…”
Section: Ici‐induced Iraesmentioning
confidence: 99%
“…Yet there is also an observation that the development of autoantibodies after ICI treatment may portend more severe irAEs, this has been described in most depth in the context of ANA seroconversion. 45 Lastly, there is also evidence that ICI influence the B-cell compartment and that these changes may promote ICI-induced irAEs. 46 Das et al 47 observed a reduction in circulating B cells in patients with melanoma after ICI therapy and that this was associated with greater risk of ICI-induced irAEs as well as irAE severity.…”
Section: Autoantibodies and The Development Of Ici-induced Iraesmentioning
confidence: 99%
“…However, the results were somewhat inconsistent when investigating which specific autoantibody was the main contributor to the association with irAEs. The most promising and well-studied autoantibody was anti-nuclear antibody [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], followed by rheumatoid factor [ 13 , 22 ], both studied in multiple types of solid tumors, including malignant melanoma and NSCLC. Some studies suggested a positive association between pre-existing autoantibodies and the development of any irAE [ 14 , 16 , 17 , 18 , 19 ], but some reported no association [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…The most promising and well-studied autoantibody was anti-nuclear antibody [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], followed by rheumatoid factor [ 13 , 22 ], both studied in multiple types of solid tumors, including malignant melanoma and NSCLC. Some studies suggested a positive association between pre-existing autoantibodies and the development of any irAE [ 14 , 16 , 17 , 18 , 19 ], but some reported no association [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In summary, the evidence is conflicting, and they do not seem to be a reliable predictor for irAE in general when used alone.…”
Section: Biomarkersmentioning
confidence: 99%